Coping behavior on e-banking users: perceived threat and anxiety - Mahardika, Arya Samudra (Proceeding International Conference on Accounting and Finance, 2023)
The purpose of this study was to empirically test the relationship between perceived threat and anxiety on coping behaviors (protective action, seeking help, avoidance) of e-banking users in Kebumen district. 121 research samples were obtained by distributing questionnaires via a google form. The sampling technique in this study used purposive sampling with the criteria of respondents using e-banking. Hypothesis testing in this study uses structural equation modeling through the WarpPLS version 7.0 software. The results of hypothesis testing show that perceived threats and anxiety are empirically proven to have an effect on coping behavior; however, there is no support for perceived threats to avoidance. The results of this study indicate that threats do not influence respondents to use e-banking, because it has become a daily necessity.